2022
DOI: 10.1111/jan.15218
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ approach to pressure injury prevention: A descriptive qualitative study

Abstract: Aims To explore Registered Nurses' approaches to pressure injury prevention, including how they perceive their roles, how they prioritize pressure injury prevention and factors influencing prevention in the Chinese context. Design A qualitative descriptive study. Methods Audio‐recorded, face‐to‐face, semi‐structured individual interviews were conducted with Registered Nurses in a large tertiary hospital in China from August to December 2020. Using the System Engineering Initiative for Patient Safety Model, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 62 publications
(92 reference statements)
0
23
0
Order By: Relevance
“…Each study was evaluated for methodological quality using the MMAT (Hong et al, 2018), encompassing qualitative and quantitative descriptive criteria. Across the six studies (Hoviattalab et al, 2014; Latimer et al, 2016, 2021; Li et al, 2021, 2022; McInnes et al, 2013), methodological quality was high; however, all presented with limitations (Table 4). Three quantitative studies identified a risk of bias (Hoviattalab et al, 2014; Li et al, 2021; McInnes et al, 2013), whilst the trustworthiness of the qualitative studies was well reported (Latimer et al, 2021; Li et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each study was evaluated for methodological quality using the MMAT (Hong et al, 2018), encompassing qualitative and quantitative descriptive criteria. Across the six studies (Hoviattalab et al, 2014; Latimer et al, 2016, 2021; Li et al, 2021, 2022; McInnes et al, 2013), methodological quality was high; however, all presented with limitations (Table 4). Three quantitative studies identified a risk of bias (Hoviattalab et al, 2014; Li et al, 2021; McInnes et al, 2013), whilst the trustworthiness of the qualitative studies was well reported (Latimer et al, 2021; Li et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Nurses approach to PIP education delivery is guided by a self‐perceived sense of responsibility to prioritise (Latimer et al, 2021; Li et al, 2022), guide, raise awareness and implement PIP strategies for patients in their care (Latimer et al, 2021). Whilst nurses rely on hospital policy and clinical practice guidelines to support PIP practice (Li et al, 2022), up‐to‐date knowledge is required by nurses to facilitate delivery (Li et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, clinical nurses play an important role in preventing and managing pressure injuries. They should be able to use evidence‐based practices and accepted risk assessment tools to assess a patient's risk of exacerbated injuries (Huang et al, 2021; Li et al, 2022; Mitchell, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, pressure injury risk assessment and prevention interventions should be promoted through continuing education regarding pressure injuries for health professionals including nurses (Li et al, 2022; Porter‐Armstrong et al, 2018). Above all, pressure injuries of patients admitted to wards after general anesthesia occur immediately after surgery rather than progressing over time.…”
Section: Discussionmentioning
confidence: 99%